Attitudes of Turkish Medical and Law Students towards the Organ Donation - Sağiroğlu, M. (Int J Organ Transplant Med, 2015)
Background: Attitudes of medical and law personnel towards organ donation are very important. Objective: To compare the attitudes of the medical and law students towards organ donation. Methods: 498 students in the 1(st) and 4(th) grades of the medical and law faculties of Erciyes University, Kayseri, Turkey, in 2011–12 academic year, were included in this study. A questionnaire consisting of 31 questions on socio-demographic characteristics of the students and their attitudes towards organ donation and transplantation was administered to the participants. Results: The percentage of the students who donated organs was 1%. Approximately, 48% of the medical students and 34% of the law students stated that they think to donate organs. The percentage of the students with a positive attitude towards organ donation was found significantly higher among the medical students than the law students, and higher among the 4th grade compared to the 1(st) grade. Conclusion: The percentages of the students who have donated organs and think to donate are rather low. Medical students’ attitude towards organ donation was more positive than the law students.